SARS-CoV-2 nsp14 Exoribonuclease Removes the Natural Antiviral 3′-Deoxy-3′,4′-didehydro-cytidine Nucleotide from RNA - Nicholas H. Moeller; Kellan T. Passow; Daniel A. Harki; Hideki Aihara (Viruses, 2022)
The on-going global pandemic of COVID-19 is caused by SARS-CoV-2, which features a proofreading mechanism to facilitate the replication of its large RNA genome. The 3′-to-5′ exoribonuclease (ExoN) activity of SARS-CoV-2 non-structural protein 14 (nsp14) removes nucleotides misincorporated during RNA synthesis by the low-fidelity viral RNA-dependent RNA polymerase (RdRp) and thereby compromises the efficacy of antiviral nucleoside/nucleotide analogues. Here we show biochemically that SARS-CoV-2 nsp14 can excise the natural antiviral chain-terminating nucleotide, 3′-deoxy-3′,4′-didehydro-cytidine 5′-monophosphate (ddhCMP), incorporated by RdRp at the 3′ end of an RNA strand. Nsp14 ExoN processes an RNA strand terminated with ddhCMP more efficiently than that with a non-physiological chain terminator 3′-deoxy-cytidine monophosphate (3′-dCMP), whereas RdRp is more susceptible to chain termination by 3′-dCTP than ddhCTP. These results suggest that nsp14 ExoN could play a role in protecting SARS-CoV-2 from ddhCTP, which is produced as part of the innate immune response against viral infections, and that the SARS-CoV-2 enzymes may have adapted to minimize the antiviral effect of ddhCTP.